Effect of Mobile Banking on Performance of Microfinance Banks in Kenya - Ndirangu, Eunice; Kimani, John (European Journal of Business and Strategic Management, 2022)
Purpose: The purpose of this study was to establish the effect of mobile banking on performance of microfinance banks in Kenya Methodology: The study adopted positivism philosophy approach and descriptive research design was used. The study also used census survey. The target population was the thirteen Microfinance Banks regulated by the Central Bank of Kenya. The questionnaires were self-administered and primary data was collected from the thirteen regulated microfinance banks. The data was analyzed using the Statistical Package for Social Science. Descriptive and inferential statistics were used for preliminary analysis. Factor analysis was conducted to reduce the number of factors and Kaiser Mayer Olkin and Barlett's test of Sphericity were tested and total variance explained, scree plot and rotated component matrix were drawn. Findings: The findings showed that majority of the respondents were in agreement that it is easy to deposit and withdraw cash, transfer funds, apply loan and check the balance using mobile banking. The hypothesis (H02) findings showed that mobile banking had a significant effect on performance of MFBs. The summary model showed that the R was 0.280 and R square of 0.078. This implied that mobile banking predicted 7.8% of the performance of MFBs. The ANOVA results showed that F value was 4.940 and a p value of 0.030 which indicates that it was statistically significant. After the T test mobile banking beta coefficient was the regression model was generated Y = 2.841+ 0.271MBA. Unique Contribution to Theory, Practice and Policy: The study recommends that MFBs should partner with telecommunication services providers to develop products and services which are customer oriented and easy to use. They should develop strategies on market penetration by creating awareness on the product and services available in the market.